Plastic harmful ingredients reduce the level of neurofilament light chain protein - Long Li; Xiaoxiu Ma; Junwei Liu; Yongli Wu (Ecotoxicology and Environmental Safety)
Population exposure to plastics is increasing, and plasticizers are frequently detected in humans as important ingredients of plastic products. However, patterns of exposure to harmful ingredients of plastics and their effects on neurofilament light chain (NFL), a marker of active brain pathology, are currently inconclusive. Herein, we employed a range of statistical methods to thoroughly investigate the impact of 24 plastic hazardous ingredients and their varying exposure patterns on NFL concentrations in the blood of the general population in 533 participants. Generalized linear model revealed a positive correlation between Mono-isononyl phthalate and Mono (2-Ethyl- 5-Hydroxyhexyl) Phthalate (MEHHP) with NFL. Furthermore, a significant dose-response relationship was observed between MEHHP and NFL, while Butyl paraben and Mono (Hydroxy-Isononyl) Ester exhibited a distinct ''inverted U-shaped'' nonlinear pattern with NFL. Additionally, Weighted Quantile Sum model allowed us to identify the mixed effects of all 24 plastic hazardous ingredients, with Mono(2-Ethyl-5-Oxohexyl) Phthalate, Mono-isobutyl phthalate, Mon butyl Phthalate, Propyl paraben and Triclosan occupying prominent positions. Finally, the latent profile analysis categorized exposures into high, medium, and low patterns, confirming that higher exposure to plastic hazardous ingredients posed a significant risk factor for elevated NFL levels in the blood. Exposure to plastic hazardous ingredients significantly increases the risk of NFL, the present contributes to early detection and intervention to reduce the incidence of neurodevelopmental disorder.